Female football fans or football fangirls? : A study on how female football fans in Singapore negotiate their identity as women and as fans through their social experiences. - Nur Syahirah Jasni. (2013)
This thesis explored how female football fans in Singapore, being marginalized and excluded from the male dominated football arena, negotiated their identity as both a woman and a fan. Based on these women’s experiences, I embarked on a micro-sociological study to unravel and discover the ways in which these women struggled to identify as a woman and a fan, and I suggested framing female football fans in Singapore as a subcultural group and how there is an importance of having a clear identification of the difference between a female football fan and a football fangirl. The social experiences of these women were not isolated experiences, in fact, they later pointed out towards the existing larger social phenomena of gender discrimination in football.